The Diary of Vaslav Nijinsky Book review - Anderson, Jack 1935- (Dance Books Ltd., Alton,Hampshire (UK), 1999)
"I do not like Zurich, because it is a dry town. It has a lot of factories and many business people. I do not like dry people, and therefore I do not like business people". PALABRAS CLAVE: Vaslav Nijinsky's diary.
The Diary of Vaslav Nijinsky: Unexpurgated Edition. Joan Acocella (ed.), Farrar, Straus & Giroux, 1999.